2015
DOI: 10.4018/978-1-4666-7476-9.ch013
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming Corporate Social Responsibility at the Core of the Business School Curriculum

Abstract: Extant literature has highlighted that business schools have been accused of promoting an educational ethos that emphasizes shareholder value and the pursuit of short-term profits, thereby preparing overly competitive future generations interested in profit maximization. This chapter highlights the importance of integrating CSR into the mainstream of business schools' curricula, arguing for the responsible role that business schools should play and emphasizing the strategic case for such integration. The chapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Analysis of the expert's survey revealed that the weight given to the complexity of CSR issues was 0.08, which affects the effectiveness of CSR implementation in a moderate way. The relationship between society and business is very complex in nature (Jamali and Abdallah, 2015). CSR is multidimensional in nature and focuses on various activities of organizations, even as it touches the various facets of society (Goyal and Kumar, 2017;Bhardwaj, 2016;Polonsky and Jevons, 2009;Muller, 2006), because it incorporates various issues focusing on different stakeholders (Kleine and von Hauff, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the expert's survey revealed that the weight given to the complexity of CSR issues was 0.08, which affects the effectiveness of CSR implementation in a moderate way. The relationship between society and business is very complex in nature (Jamali and Abdallah, 2015). CSR is multidimensional in nature and focuses on various activities of organizations, even as it touches the various facets of society (Goyal and Kumar, 2017;Bhardwaj, 2016;Polonsky and Jevons, 2009;Muller, 2006), because it incorporates various issues focusing on different stakeholders (Kleine and von Hauff, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Key critiques of business schools have ranged from the failings of the management theory taught by business schools (Ghoshal, 2005) and how they prepare students for the future (Cornuel, 2007;Starkey & Tempest, 2005), to how business schools are, or are not responding to the challenges arising from societal issues, such as sustainability (Boyle, 2004;Schoemaker, 2008) and responsibility in management education (Cornuel & Hommel, 2015). Recent debates on the role of business schools have highlighted the need for greater societal engagement and for incorporating sustainability and corporate social responsibility (CSR) into business schools' remit, and in particular embedding it in the curriculum taught in business schools (Hommel & Thomas, 2014;Jamali & Abdallah, 2015). In this paper we explore the organizational and strategic factors that influence whether sustainability becomes successfully embedded in business schools, which have explicit sustainability commitments.…”
Section: Decoupling Introductionmentioning
confidence: 99%
“…Other researchers have suggested that business schools are reaching a "tipping point" (Hommel & Thomas, 2014:7), which will see business schools change, and redefine or rebuild their legitimacy by addressing and integrating CSR and sustainability in the business school curriculum (Hommel & Thomas, 2014;Jamali & Abdallah, 2015). While earlier work has identified potential determinants of sustainability implementation in practice (Matter & Moon, 2004), this paper contributes to the debate through an analysis of the combinations of organizational and strategic characteristics that mean business schools "walk their talk" (Rasche & Gilbert, 2015:248) and tightly couple, rather than decouple their espoused sustainability commitments from their actual practice.…”
Section: Decoupling Introductionmentioning
confidence: 99%
“…Such diversity in the adoption of sustainable business education can be explained in part through the various strategic, structural and cultural barriers faced by proponents in different settings (Solitander et al 2012). For example, research shows that the legitimacy of sustainability topics is often disputed (Hommel and Thomas 2014), and that sustainability is routinely misunderstood and underappreciated among business school educators (Jamali and Abdallah 2015). And despite the pressure from accreditation agencies to embed sustainability across business school programmes, clear templates for the design and implementation of sustainability education are hard to come by (Rasche and Gilbert 2015).…”
Section: Introductionmentioning
confidence: 99%